Determination of Plastic Limit of Some Selected Soils Using Rolling Device (Progressive Agriculture, 2013)
An attempt was made to fabricate a rolling device for determining the plastic limit of different loamy and clay soils. Five different types of soil collected from different location were used for the present investigation. Clay was taken as the yardstick of converting the soil as a continuous particle and measuring scale of this continuity was expressed in terms of clay ratio. Thus plastic limit of the soils were determined by following rolling device, Casagrande method and cone penetrometer method. It was observed that plastic limit determined by different methods have similar values for different soils and clay ratio has played important role in varying the values. Plastic limit varied from almost 20 to 25% for loamy soil having clay ratio 0.30 to 0.40 and almost 25 to 30% for clay soils having clay ratio 0.75 to 0.78. The results revealed that values of plastic limit by rolling device method were on an average 5% less than that of Casagrande method and almost same to that of the cone penetrometer method at different levels of clay ratio. However, the construction of rolling device has been found easy and economical. It provides perfect terminal point for accurate result. Hence it is a reliable technique for determining soil plastic limit for cohesive soil. But it is not a workable means for non-cohesive soil.DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16767 Progress. Agric. 21(1 & 2): 187 - 194, 2010